GE_GERICHTE C/3684/2014 vom 19. Mai 2016 - GE Cour de justice (2016)
CONSTATATION DES FAITS ; DROIT D'ÊTRE ENTENDU ; RÉSILIATION IMMÉDIATE ; EFFICACITÉ ; ANNULABILITÉ ; RÉSILIATION ABUSIVE | CO.257.f.3; CO.271.1;